L-Arabinose Transport and Metabolism in Salmonella Influences Biofilm Formation - Vasicek, Erin M.; O’Neal, Lindsey; Parsek, Matthew R.; Fitch, James; White, Peter; Gunn, John S. (Frontiers in Cellular and Infection Microbiology, 2021)
L-arabinose inducible promoters are commonly used in gene expression analysis. However, nutrient source and availability also play a role in biofilm formation; therefore, L-arabinose metabolism could impact biofilm development. In this study we examined the impact of L-arabinose on Salmonella enterica serovar Typhimurium (S. Typhimurium) biofilm formation. Using mutants impaired for the transport and metabolism of L-arabinose, we showed that L-arabinose metabolism negatively impacts S. Typhimurium biofilm formation in vitro. When L-arabinose metabolism is abrogated, biofilm formation returned to baseline levels. However, without the ability to import extracellular L-arabinose, biofilm formation significantly increased. Using RNA-Seq we identified several gene families involved in these different phenotypes including curli expression, amino acid synthesis, and L-arabinose metabolism. Several individual candidate genes were tested for their involvement in the L-arabinose-mediated biofilm phenotypes, but most played no significant role. Interestingly, in the presence of L-arabinose the diguanylate cyclase gene adrA was downregulated in wild type S. Typhimurium. Meanwhile cyaA, encoding an adenylate cyclase, was downregulated in an L-arabinose transport mutant. Using an IPTG-inducible plasmid to deplete c-di-GMP via vieA expression, we were able to abolish the increased biofilm phenotype seen in the transport mutant. However, the mechanism by which the L-arabinose import mutant forms significantly larger biofilms remains to be determined. Regardless, these data suggest that L-arabinose metabolism influences intracellular c-di-GMP levels and therefore biofilm formation. These findings are important when considering the use of an L-arabinose inducible promoter in biofilm conditions.